Analysis of properties of modified kaolins and water-dispersion paints developed on their base - Merezhko, Nina; Sirenko, Svitlana; Shulga, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
Analysis of the effect of modified kaolins on the formation of properties of waterdispersed paints was conducted. It was determined that, as a result of the kaolin modification by 3aminopropyltriethoxysilane, their adsorption and physical and chemical properties (wettability and specific effective surface by water and benzene) were changed. Specific effective surface of kaolin from Glukhovetskiy deposit was increased by benzene by 26.47 %, from Prosianivskiy deposit – by 5.9 %. The same indicator by water was decreased by 26.1 % for the kaolin from Glukhovetskiy deposits and 3.4 % for the kaolin from Prosianivskiy deposit. The adsorption of acrylicstyrene polymer by respective kaolins was increased by 32.1 % and 23.8 %. The processes of interaction of kaolins with a modifier and styreneacrylic film former were studied; the parameters of the main characteristic bands responsible for valence fluctuations of reactive capable groups of kaolins and film former were analyzed. The results of the study demonstrated that, due to the modification of kaolins by 3aminopropyltriethoxysilane, their polymeric philicity was increased. The premodified kaolins, characterized by the most complete interaction with styreneacrylic film former, are proposed to use as fillers for waterdispersion paints. This will ensure the higher performance properties of paints and coatings: elasticity at the level of 2–4 mm, the edge angle of wetting at the level of 89–95 degrees, tensile strength in the range of 5.53–6.81 MPa, which is by 18–51 % larger than when using nonmodified fillers. It was determined that improving the compatibility of kaolins with the film former of waterdispersion paints allow forming coatings more resistant to corrosive liquids, with low water absorption at the level of 8.1–9.7 % mass %, i. e., by 17.9 % – 10.4 lower than when adding nonmodified kaolins.